Acetone facilitated DNA sampling from electrical tapes improves DNA recovery and enables latent fingerprints development. (July 2017) - Feine, Ilan; Shpitzen, Moshe; Geller, Boris; Salmon, Eran; Peleg, Tsach; Roth, Jonathan; Gafny, Ron
Highlights: A novel touch DNA recovery protocol from electrical tapes (ETs) was developed. The protocol involves a simple two-step acetone–water procedure. This protocol increased DNA yield by up to 70% compared to direct recovery. In addition, it allows latent fingerprints development from the non-adhesive side of ETs. Abstract: Electrical tapes (ETs) are a common component of improvised explosive devices (IEDs) used by terrorists or criminal organizations and represent a valuable forensic resource for DNA and latent fingerprints recovery. However, DNA recovery rates are typically low and usually below the minimal amount required for amplification. In addition, most DNA extraction methods are destructive and do not allow further latent fingerprints development. In the present study a cell culture based touch DNA model was used to demonstrate a two-step acetone–water DNA recovery protocol from ETs. This protocol involves only the adhesive side of the ET and increases DNA recovery rates by up to 70%. In addition, we demonstrated partially successful latent fingerprints development from the non-sticky side of the ETs. Taken together, this protocol maximizes the forensic examination of ETs and is recommended for routine casework processing.